Decision-making in case of an unintended pregnancy: an overview of what is known about this complex process - Eline W. Dalmijn; Merel A. Visse; Inge van Nistelrooij (Taylor & Francis Group, 2024)
AbstractIntroduction: Unintended pregnancies are a worldwide health issue, faced each year by one in 16 people, and experienced in various ways. In this study we focus on unintended pregnancies that are, at some point, experienced as unwanted because they present the pregnant person with a decision to continue or terminate the pregnancy. The aim of this study is to learn more about the decision-making process, as there is a lack of insights into how people with an unintended pregnancy reach a decision. This is caused by 1) assumptions of rationality in reproductive autonomy and decision-making, 2) the focus on pregnancy outcomes, e.g. decision-certainty and reasons and, 3) the focus on abortion in existing research, excluding 40% of people with an unintended pregnancy who continue the pregnancy. Method: We conducted a narrative literature review to examine what is known about the decision-making process and aim to provide a deeper understanding of how persons with unintended pregnancy come to a decision.Results: Our analysis demonstrates that the decision-making process regarding unintended pregnancy consists of navigating entangled layers, rather than weighing separable elements or factors. The layers that are navigated are both internal and external to the person, in which a 'sense of knowing' is essential in the decision-making process. Conclusion: The layers involved and complexity of the decision-making regarding unintended pregnancy show that a rational decision-making frame is inadequate and a more holistic frame is needed to capture this dynamic and personal experience.